Gender Representation In Youtube Advertisements Through Critical Literacy In Education - Novia Mudzayyanah; Agus Darma Yoga Pratama; Ni Kadek Amanda Astuti Dewi (Institut Pariwisata dan Bisnis Internasional, 2026)
Digital media have become an important part of students' learning environments, shaping how learners access information and interpret social realities (Hatlevik et al., 2021; Pangrazio & Sefton-Green, 2022) exposing them not only to educational content but also to ideologically loaded media such as advertisements. Among digital platforms, YouTube plays a significant role in shaping students’ perceptions through its pervasive advertising content. This study investigates how gender representation is constructed in YouTube advertisements and examines its implications for students’ critical literacy in educational contexts. Employing a qualitative descriptive research design, the study analyzes eight YouTube advertisements from diverse product categories using Fairclough’s (1995) Critical Discourse Analysis framework, focusing on textual, discursive, and social practice dimensions. The findings reveal recurring gendered patterns in which home cleaning and domestic products are predominantly associated with female characters, while luxury, automotive, and technology-related products are more frequently represented through male figures. These representations reinforce conventional gender ideologies that link femininity with caregiving, emotional labor, and appearance, and masculinity with agency, productivity, and public success. The study argues that critical literacy practices are essential for raising students’ awareness of gendered social values embedded in digital advertising, enabling them to question dominant representations and develop more inclusive and equitable perspectives on gender.